The Twin Transition Strategy Framework: How Universities Can Effectively Leverage Their Capabilities In Research, Teaching, And Collaborations - Kyawt Ni, Anna (Community Notebook. People, Education and Welfare in the Society 5.0, 2025)
The twin transition (digital and ecological transformations) is crucial for addressing sustainable growth within Higher Education (HE). This conceptual paper proposes a Twin Transition Strategy Framework for Higher Education institutions, focusing on how universities can leverage their research, teaching, and collaboration capabilities to address sustainable growth through digital and ecological transformations. The framework identifies four key entities: Research Culture, University Curricula, University-Industry Partnerships, and University-Government Partnerships. It highlights significant opportunities for universities, including pioneering interdisciplinary research and adapting curricula, while also acknowledging challenges like potential conflicts between digital and environmental goals. The paper advocates for a holistic, integrated approach, emphasizing innovative teaching, strong partnerships, and ambitious sustainability targets for university operations, ultimately offering recommendations for contributing to a sustainable and digital future.